2022
DOI: 10.2147/jir.s366204
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myosteatosis is Associated with Systemic Inflammation and a Loss of Muscle Bioenergetics in Stable COPD

Abstract: Background: Common features among patients with more advanced chronic obstructive pulmonary disease (COPD) are systemic inflammation and a loss of both muscle mass and normal muscle composition. In the present study, we investigated COPD subjects to better understand how thigh muscle fat infiltration (MFI) and energy metabolism relate to each other and to clinical features of COPD with emphasis on systemic inflammation. Methods: Thirty-two Caucasians with stable COPD were investigated using questionnaires, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Capillarization has notably been found impaired specifically in type I muscle fibers, which has a deep impact on the muscle’s oxidative capacity [ 14 , 15 ]. Adipose tissue infiltration has also been reported in COPD muscle, in a similar way to senescent muscle in the aging population, particularly in the obese sarcopenic phenotype where adipose inflammation leads to the redistribution of fat to the intra-abdominal area and skeletal muscle tissue [ 16 , 17 ] ( Figure 1 ).…”
Section: Histopathological Alterations Of Copd Skeletal Muscle Tissuementioning
confidence: 82%
“…Capillarization has notably been found impaired specifically in type I muscle fibers, which has a deep impact on the muscle’s oxidative capacity [ 14 , 15 ]. Adipose tissue infiltration has also been reported in COPD muscle, in a similar way to senescent muscle in the aging population, particularly in the obese sarcopenic phenotype where adipose inflammation leads to the redistribution of fat to the intra-abdominal area and skeletal muscle tissue [ 16 , 17 ] ( Figure 1 ).…”
Section: Histopathological Alterations Of Copd Skeletal Muscle Tissuementioning
confidence: 82%
“…When muscle wasting occurs, the expression levels of pro-inflammatory cytokines and their receptors are upregulated, leading to metabolic disturbances in muscle tissue ( 25 ), ultimately resulting in sarcopenia ( 26 ). Besides muscle wasting, patients with more severe COPD often have deposits of ectopic fat, including visceral adipose tissue, and muscle fat infiltration; both of which are associated with elevated markers of systemic inflammation ( 12 ). Clinical studies have found increased levels of interleukin (IL)-6, IL-10, hypersensitive C-reactive protein (CRP), and tumor necrosis factor (TNF)-α in patients with coexisting COPD and sarcopenia ( 27 , 28 ).…”
Section: Pathogenesismentioning
confidence: 99%
“… 5 Metabolic disturbances of cells’ handling of iron, relevant for the resistance against oxidative damage, 6 , 7 and muscle tissue bioenergetics, important for normal muscle function, are some mechanisms implicated in COPD pathogenesis. 8 …”
Section: Introductionmentioning
confidence: 99%
“…5 Metabolic disturbances of cells' handling of iron, relevant for the resistance against oxidative damage, 6,7 and muscle tissue bioenergetics, important for normal muscle function, are some mechanisms implicated in COPD pathogenesis. 8 Possibly, due to a progression from a local airway inflammation to a systemic one, COPD may involve muscle cells in skeletal muscles, causing myosteatosis, which in turn trigger BaPA by a reduced physical performance. 8,9 In addition to common risk factors, such as smoking and advanced age, a low-grade systemic inflammation is thought to be involved in the pathogenesis of chronic heart failure (CHF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation